Four-coordinate nickel(ii) and copper(ii) complex based ONO tridentate Schiff base ligands: synthesis, molecular structure, electrochemical, linear and nonlinear properties, and computational study12. Issue 41 (28th September 2015) - Novoa, Néstor; Roisnel, Thierry; Hamon, Paul; Kahlal, Samia; Manzur, Carolina; Ngo, Hoang Minh; Ledoux-Rak, Isabelle; Saillard, Jean-Yves; Carrillo, David; Hamon, Jean-René
Abstract : The properties of NLO active ternary Ni(ii )- and Cu(ii )-unsymmetrical Schiff base complexes were explored in concert with DFT calculations. Abstract : We report the synthesis, characterization, crystal structures, nonlinear-optical (NLO) properties, and density functional theory (DFT) calculations of nickel(ii ) and copper(ii ) complex based ONO tridentate Schiff base ligands: two mononuclear compounds, [Ni(An-ONO)(NC5 H5 )] (5 ) and [Cu(An-ONO)(4-NC5 H4 C(CH3 )3 )] (6 ), and two heterobimetallic species, [M(Fc-ONO)(NC5 H5 )] (M = Ni, 7 ; Cu, 8 ), where An-ONOH2 (3 ) and Fc-ONOH2 (4 ) are the 1 : 1 condensation products of 2-aminophenol and p -anisoylacetone and ferrocenoylacetone, respectively. These compounds were characterised by microanalysis, FT-IR and X-ray crystallography in the solid state and in solution by UV-vis and 1 H and 13 C NMR spectroscopy. The crystal structures of3–5, 7 and8 have been determined and show for Schiff base complexes5, 7 and8 a four-coordinated square-planar environment for nickel and copper ions. The electrochemical behavior of all derivatives3–8 was investigated by cyclic voltammetry in dichloromethane, and discussed on the basis of DFT-computed electronic structures of the neutral and oxidized forms of the compounds. The second-order NLO responses of3–8 have been determined by harmonic light scattering measurements using a 10 −2 M solution of dichloromethane and working with a 1.91 μm incident wavelength, giving rather high β 1.91 values of 350 and 290 × 10 −30 esu for the mononuclear species5 and6, respectively. The assignment and the nature of the electronic transitions observed in the UV-vis spectra were analyzed using time-dependent (TD) DFT calculations. They are dominated by LMCT, MLCT and π–π* transitions.